NEEDS ANALYSIS FOR THE CURRICULUM DESIGN OF ENGLISH INVOLVING GENERAL DUTY NURSING COLLEGE STUDENTS: THE CASE OF KINSHASA-DRC - Flory MANDINA MUANA MUNDELE; Albin MAJAMBO KALONDA; Simon-Decap MABAKUTUVANGILANGA NTELA (Cahiers Africains des Droits de l’Homme et de la Démocratie ainsi que du Développement Durable)
The teaching of English for specific purposes has been a real challenge for ESP practitioners for a long time. Among difficulties encountered by experts working on ESP studies, the lack of appropriate material has been one of the most worrying issues. Not having a suitable curriculum for teaching can surely make ESP courses inadequate. Therefore, curriculum design has become an interesting field of investigation drawing the attention of many researchers who focus their studies on English for specific purposes. Ignoring the learners’ needs while designing a curriculum of English for specific purposes will obviously lead to a curriculum not satisfying learners and all people involved in the learning process. This article aimed at assessing the needs for the curriculum design of English involving general duty nursing college students of Kinshasa. The question asked was to know what general duty nursing college students of Kinshasa really need to study in English. To that end, finding main topics to include in the English course program for general duty nursing college students of Kinshasa was the main concern of this study. The research design was qualitative with triangulated data sources using individual unstructured interviews. Due to the size of the sample and the kinds of data collected technology through ATLAS.ti software was used to analysis recordings’ transcripts effectively. The respondents included in the study were 104: 47 third-year general duty nursing college students, 31 nurses having some workplace English language experience, 21 experienced nursing content teachers, and 5 stakeholders. The result has revealed that the course content to teach to general duty nursing college students from Kinshasa should include the main topics emerged from the analysis of the raw data. Those topics are related to the real nursing professional and academic contexts. They range from specific linguistic tasks on nursing real-life activities to providing specific English knowledge needed to read professional documents, including books and articles, and to participate in professional trainings and conferences held in English effectively. Referring to those themes, an appropriate curriculum can be designed. It has been proved that to design an English course program meeting the real needs and expectations of students, teachers of English and all people associated with the program should work together in the path of needs analysis study leading to curriculum design. Underestimating students’ needs and stakeholders’ expectations will result in a course curriculum irrelevant to the learners’ goals for learning and to the expectations of all the people involved in the learning process.